A Cost‐Efficient Fabrication Strategy for Conductive Ti2AlC Honeycomb Monolith Using Elemental Powders1. Issue 9 (11th March 2015) - Fang, Xuanming; Wang, Xiaohui; Zhang, Hui; Li, Zhaojin; Li, Jialin; Zhou, Yanchun
<x xml:space="preserve">Abstract</x> A cost‐efficient strategy using elemental powders of Ti, Al, and graphite as starting materials is proposed to fabricate conductive Ti2AlC honeycomb monolith. The honeycomb structure is extruded from a plastic feed material composed of the initial powders and several additives. Phase‐pure Ti2AlC can be obtained with a direct heating schedule, but the shape of the extruded green body will be destroyed due to thermal explosion in Ti−Al−C strongly exothermic system, which is resulted from the rapid release of latent heat from reactions between the elemental powders during heating process. To avoid the thermal explosion, the honeycomb sample is dwelled at 650 °C for 2 h to release latent heat in a controlled manner. As a result, Ti2AlC honeycomb monolith with designed structure is obtained, followed by sintering at elevated temperatures. In addition, the phase evolution and mechanism for pore formation are discussed.